2020
DOI: 10.13106/jafeb.2020.vol7.no4.51
|View full text |Cite
|
Sign up to set email alerts
|

Does Hedging with Derivatives Affect Future Crash Risk?

Abstract: The study aims to investigate the relationship between hedging with derivatives and subsequent firm-level stock price crash risk. Our sample consists of KOSPI-and KOSDAQ-listed companies from 2004 to 2014. The total firm-year observation is 4,886. We find that hedging with derivatives is related to greater possibilities of crash risk. The results suggest that the complexity of economic and financial reporting for derivatives may aggravate the company's information opacity, ultimately increasing the crash risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…BFE also has affected NPLs significantly at level 1% which means more members with financial expertise on the board of directors can strongly reduce NPLs. Our finding is consistent with the study of Pham (2021), which found that BFE affected the risk negatively in the banks of Vietnam. Moreover, RMC has significant negative impacts on NPLs at level 5%.…”
Section: Hypotheses Testsupporting
confidence: 93%
See 1 more Smart Citation
“…BFE also has affected NPLs significantly at level 1% which means more members with financial expertise on the board of directors can strongly reduce NPLs. Our finding is consistent with the study of Pham (2021), which found that BFE affected the risk negatively in the banks of Vietnam. Moreover, RMC has significant negative impacts on NPLs at level 5%.…”
Section: Hypotheses Testsupporting
confidence: 93%
“…Alternatively, these financial experts can regularly identify more calculated risks to shareholders and encourage management to take on those risks (Minton et al, 2014;Tariq et al, 2021). Pham (2021) pointed out the negative influence of board financial expertise on credit risk measured by non-performing loans in Vietnam banks during 2007-2018. Hence, the study hypothesises that: H2: Board financial experience influences non-performing loans negatively.…”
Section: Board Financial Experience and Non-performing Loansmentioning
confidence: 99%
“…The increase in the volatility of the spot market after the introduction of the futures contracts can be explained as a result of high degree of leverage and the participation of speculative traders in the futures markets. Moreover, Park and Park (2020) investigate the impact of hedging with derivatives on firm-level crash risk in Korea. The results derived from this study indicate that hedging with derivatives leads to greater possibility of future crash risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Four main tools have been applied, including (i) forward contracts, (ii) future contracts, (iii) option contracts, and (iv) swap contracts. In principle, these are the hedging tools used to boost the corporate value (Park & Park, 2020). However, all businesses that use derivatives' financial instruments must measure these instruments, show that they are understandable, and compare risks when being shown in the financial statements (Abdel-khalik & Chen, 2015).…”
mentioning
confidence: 99%
“…However, all businesses that use derivatives' financial instruments must measure these instruments, show that they are understandable, and compare risks when being shown in the financial statements (Abdel-khalik & Chen, 2015). Multinational companies have applied SFAS 133 to enhance their transparency, to provide information on the actual situation that corresponds to the hedging tools, keep updated when using derivatives, and measuring them at fair value in the reports (Park & Park, 2020;Wang et al, 2005).…”
mentioning
confidence: 99%